Location, knowledge sourcing and innovation - Evidence from the ICT sector in Austria - Markus Grillitsch; Christoph Höglinger; Franz Tödtling (European Regional Science Association (ERSA), 2010)
The competitiveness of many of today's industries largely depends on the ability to innovate. Innovation is nowadays regarded as a result of an open and interactive knowledge process, demanding from companies to generate, absorb and apply knowledge relying both on internal and external sources. Companies often maintain links to a large variety of knowledge sources and partner types on different geographic levels and they use different mechanisms for acquiring knowledge from these sources. In addition, the location of companies is thought to have an important impact on innovativeness through potential regional knowledge links and accessibility to interregional ones. The location of a company in a "thick" Regional Innovation System (RIS) should lead to a better performance as compared to a location in a "thin" RIS. Conceptually, the paper aims to develop a better understanding of the relationships and dynamics between internal knowledge and learning through external knowledge sourcing. The derived presumptions are tested by developing and applying a multivariate model that describes the impact of the above-mentioned factors on the innovativeness of firms. The importance of internal knowledge, the variety of knowledge sourcing on regional, national and international levels, the importance of cooperation as a transfer mechanism as well as the location of companies are identified as key determinants of innovativeness in knowledge-based sectors. The paper draws on data from the ICT sector in three regions in Austria. Overall, 110 personal interviews and questionnaires were collected from companies of this sector.
Keywords: 330